Свойства коммутационных ячеек, используемых в системах автоматизированного контроля - Медведик, А.Д. (Технология и конструирование в электронной аппаратуре, 2009)
Рассмотрены основные свойства коммутационных ячеек с произвольным числом выводов, на основе которых строятся регулярные коммутационные структуры. Проведен сравнительный анализ известных коммутационных структур. Розглянуто основні властивості комутаційних комірок з довільною кількістю виводів, на базі яких будуються регулярні комутаційні структури. Визначено загальну кількість можливих з.єднань між виводами при заданій кількості незалежних зв.язків, а також максимальну кількість з.єднань, які не повторюються при тих же умовах. Визначено мінімально необхідне число комутованих елементів, яке задовольняє умовам повноти з.єднань. Зроблено порівняльний аналіз відомих комутаційних структур. The main properties of commutation cells with arbitrary number of outlets have been examined. The cells of this type form the basis of regular commutation structures design. There were defined the total number of all possible contacts between the outlets at the set quantity of independent connections, and the greatest possible number of non-repeating connections for the same conditions. There was also determined the minimal necessary switched elements quantity at which the condition of connections completeness is satisfied. The comparative analysis of known commutation structures has been provided.